Preparation method of metal material with layered gradient structure
Through a comprehensive process of directional solidification, large deformation cold processing, gradient micro-zone electrical regulation and electrical pulse processing, metal materials with layered gradient structure were prepared, which solved the difficulty of metal materials in the prior art to meet high life and high service life during service in the prior art The problem of stability requirements has achieved high strength and high toughness performance improvement and production efficiency improvement.
Patent Information
- Application Number
- CN202411659497.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing metal material preparation process is difficult to meet the requirements of high-life and high stability during service of high-performance metal materials, and traditional processes are limited by material size, making it difficult to achieve performance requirements of hardness on the outside and toughness on the inside and toughness.
Directional solidification method is used to obtain slender columnar crystal blanks, and deformation structures such as high-density dislocations are obtained through large deformation cold processing. Then, it is recrystallized in combination with gradient micro-region electrical regulation processing to form an alternating distribution of "columnary crystal belt-equiaxed crystal belt" The layered gradient structure is finally introduced through electrical pulse processing with high density dislocation and fine diffuse second phase particles.
It significantly improves the strength and toughness of the material, realizes the performance requirements of hardness on the outside and toughness on the inside, solves the problem of limited material strength and plasticity improvement in traditional processes, improves production efficiency and reduces energy consumption and costs.
Smart Images

Figure CN119464691A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material preparation, and in particular relates to a method for preparing a metal material with a layered gradient structure. Background Art
[0002] With the rapid development of modern industry, especially in high-tech industries such as computers, semiconductors, instrumentation, information and communications, high load, high reliability and long service life have become the main development direction of conductor functional devices, which makes the service conditions of alloys used in signal transmission, structural support and thermal management systems more demanding, and therefore puts forward higher requirements on the mechanical properties of materials. In view of the excellent performance of metal materials such as copper alloys, aluminum alloys, titanium alloys, magnesium alloys, etc. in the manufacture of integrated circuit lead frames, precision electronic components, connectors, etc., they have become key structural functional materials in many high-tech fields. Therefore, the preparation of metal materials with ultra-high strength and good plasticity and toughness has extremely high application value and industry potential.
[0003] Improving the strength and plastic toughness of metal materials at the same time is an important way to develop high-performance metals. Fine grain strengthening and precipitation strengthening are important means to improve the mechanical properties of metal materials. By adding modifiers or rapid solidification during the smelting process, ingots with fine grains can be prepared. Through strong plastic deformation processing technologies such as equal channel extrusion, multi-directional compression, and large deformation extrusion, a fine and uniform structure of grains can be obtained. The strength and plasticity of the material can be improved at the same time by refining the grains, but the degree of strengthening is limited. Therefore, it is usually necessary to undergo appropriate heat treatment to form a large number of dispersed fine second phase particles in the alloy.
[0004] At present, there are many preparation and processing methods for high-performance metal materials, which mainly focus on the research of overall material preparation, while there are few studies on the micro-region structure control process of materials. Patent No. CN111424224B discloses a preparation method for high-strength and high-toughness conductive copper alloy strip. The method adopts the process route of "solid solution-cold rolling-electric pulse heat treatment-cold rolling-aging treatment" to make the alloy obtain a matrix with fine and uniform grains, high-density dislocations and dispersed distribution of precipitation phases, which greatly improves the mechanical properties of the alloy. However, on the one hand, this method is limited by the size of the furnace chamber in the traditional heat treatment process, the heat treatment time is long, and the production efficiency is low; on the other hand, due to the treatment of the alloy as a whole, only a single and uniformly distributed structure can be obtained. Patent No. CN110343993A discloses a hard alloy surface treatment method and application. The method adopts carburizing or nitriding treatment on the alloy surface, which can effectively improve the mechanical properties of the alloy surface. However, the process has high requirements on the thickness of the alloy. If the thickness of the substrate is too thin, the coating structure will be loose, resulting in coating failure or coating penetration. Patent CN117358754A discloses a method for preparing a composite copper-based metal strip, which is pressed and rolled after coating a tin-based or aluminum-based material layer on the graphene layer of the composite metal strip, so that the graphene layer coated on the surface of the copper-based strip and the composite copper-based metal material can be well combined, and the prepared material will not peel off or break during use, and the uniformity of the material is good, which effectively improves the conductivity of the obtained composite copper-based metal strip. However, the process has certain requirements for the thickness of the substrate, and the graphene coating is easily damaged and falls off when it is squeezed during the composite process, thereby reducing the mechanical properties and service life of the material, and the process is relatively complex and has a long process, which increases equipment cost and labor cost. Therefore, the above-mentioned process is difficult to meet the growing requirements of alloys for high life and high stability during service, so how to overcome the shortcomings of the traditional production process of metal materials, and develop a method for preparing a metal key structural material with specific performance requirements (such as hard outside and tough inside, strong and tough alternately) that is not limited by material size is very important. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the present invention provides a method for preparing a metal material with a layered gradient structure. A slender columnar crystal blank is obtained by directional solidification, and then a high-density dislocation and other deformation structure is obtained by large deformation cold working, which provides a driving force for subsequent recrystallization. The edge or core of the cold-worked material is recrystallized by combining the gradient micro-area electrical control treatment, and the structure of a specific area is precisely controlled, the matrix grain size in a specific area is quickly refined, and the work hardening in a specific area is eliminated. A layered gradient structure with alternating distribution of "columnar crystal bands-equiaxed crystal bands" is obtained, which greatly improves the strength and toughness of the material; finally, high-density dislocations and fine dispersed second phase particles are introduced simultaneously by combining electric pulse processing and treatment, thereby obtaining a high-performance metal material.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing a metal material with a layered gradient structure. The method comprises the following steps: selecting a metal raw material according to the composition of the metal material, smelting the metal raw material to obtain a metal melt, directionally solidifying the metal melt to obtain an ingot with a columnar crystal structure, cold working the ingot, performing micro-area electrical treatment on the cold-worked part to obtain a layered gradient structure material with alternating distribution of "columnar crystal bands-equiaxed crystal bands", and finally performing electrical pulse processing on the layered gradient structure material to obtain the metal material with a layered gradient structure.
[0008] In a preferred embodiment, the metal in the metal material is selected from copper alloy, iron alloy, aluminum alloy, magnesium alloy, zinc alloy, titanium alloy and the like.
[0009] In the present invention, the metal material is in the form of a plate, a strip, a wire, a tube, a special-shaped material, etc.
[0010] According to a preferred embodiment, metal raw materials are placed into a crucible in descending order according to their melting points, a covering agent is placed on the surface of the crucible, and smelting is performed to obtain a metal melt, wherein the covering agent is selected from at least one of sodium carbonate, borax, sodium fluoride, cryolite, and graphite powder.
[0011] In a preferred embodiment, the smelting process is to first melt the metal raw material at 700-2000°C, preferably 700-1800°C to obtain a melt, mechanically stir the melt, and then cool it to 650-1550°C, keep it warm for 5-10 minutes, and then apply an electric pulse to obtain a metal melt.
[0012] By adopting the above smelting process, the composition of the molten metal obtained by smelting can be uniform.
[0013] Further preferably, the rotation speed of the mechanical stirring is 0.1 to 1000 r / min, preferably 200 to 600 r / min.
[0014] Preferably, the frequency of the electric pulse is 200 to 3500 Hz, and the current density is 0.1 to 50 A / cm 3 .
[0015] More preferably, the frequency of the electric pulse is 600-2000 Hz, and the current density is 2-10 A / cm 3 .
[0016] In a preferred embodiment, the directional solidification process is as follows: the molten metal is passed through a cooling crystallizer in sequence at an axial speed of 1 to 100 mm / min, and the cooling medium used in the cooling crystallizer is selected from one of water, a gallium-indium coolant at 16°C, and a liquid nitrogen-alcohol circulating coolant, preferably a gallium-indium coolant at 16°C.
[0017] In the present invention, the liquid nitrogen alcohol circulating coolant refers to liquid nitrogen and alcohol in a ratio of 1:1 to 4. When the ratio is 1:1, it is used in situations where rapid cooling is required, and when the ratio is 1:4, it is used in situations where slow cooling is required.
[0018] In a preferred embodiment, the columnar crystal structure is selected from one of parallel, figure-eight, and vertical types, preferably parallel or figure-eight. The inventors found that when the columnar crystals are parallel, it is more convenient for subsequent micro-area control processing. When a gallium-indium coolant at 16°C is used, a parallel columnar crystal structure will be obtained through directional solidification.
[0019] Preferably, during the cold working, the working direction is controlled to be the direction of the temperature gradient.
[0020] In the present invention, by processing along the direction of the temperature gradient, the internal stress on the sample on the processed surface is in a uniform state.
[0021] In a preferred solution, during the cold working, the deformation per pass is 5% to 30%, preferably 5 to 15%, and the total deformation is 50 to 95%, preferably 80 to 95%.
[0022] In the present invention, slender columnar crystals are firstly obtained by solidification, and then high-density dislocations are obtained by large deformation cold working, which provides driving force for subsequent recrystallization.
[0023] In a preferred embodiment, the cold working is selected from one of cold rolling, cold drawing, cold forging, cold rotary forging, cold radial forging, cold extrusion and cold heading, preferably cold rolling.
[0024] A preferred solution is to divide the cold-worked billet into alternating columnar crystal regions and equiaxed crystal regions along the length direction or the width direction, and perform micro-area electrical treatment on the equiaxed crystal regions. The micro-area electrical treatment parameters are: voltage of 0.01 to 30V, preferably 0.01 to 20V, current of 0.01 to 10000A, preferably 2000 to 5000A.
[0025] In the present invention, a high-density dislocation equideformation structure is obtained by large-variable cold working, and micro-electric treatment is performed in the equiaxed crystal region. The dislocations in the columnar crystals in this region will be recrystallized to form fine equiaxed crystals, thereby converting the original columnar crystals into equiaxed crystals.
[0026] The inventors have found that this alternating distribution of "columnar crystals-equiaxed crystals" not only has higher strength and plasticity than single columnar crystals, but is also less likely to crack than single columnar crystals or equiaxed crystals during subsequent electric pulse processing.
[0027] In a preferred solution, the width ratio of the columnar crystal region to the equiaxed crystal region is 1:1 to 2. When the ratio of columnar crystal to equiaxed crystal is controlled within the above range, the performance of the final obtained material is optimal.
[0028] In a preferred solution, the current in the micro-area electrical treatment process is in the form of any one of pulse current, constant current, alternating current, direct current, etc., preferably pulse current.
[0029] According to a preferred embodiment, the micro-area electrical treatment process applies an electric current to the cold-worked workpiece through a movable electron probe, and the movable electron probe is placed in an equiaxed crystal region in the cold-worked workpiece. A current is applied once within the area of the electron probe, and then the electron probe is moved in parallel to apply a current to the next area of the electron probe. After one equiaxed crystal region is treated, the electron probe is moved to the next untreated equiaxed crystal region and the above process is repeated; the time for applying current at any one time is 0.01 to 20 minutes, preferably 0.01 to 5 minutes.
[0030] Further preferably, the shape of the electronic probe is any one of rectangular, circular, elliptical and linear.
[0031] In a preferred embodiment, the area of the electronic probe is 0.01 to 10 mm 2 .
[0032] The inventors found that through large deformation cold processing + micro-area electric pulse control processing, the grain type can be quickly controlled to make the material structure uniform, and at the same time prevent the grain growth, which not only improves the performance of the material, but also improves production efficiency and reduces energy consumption and costs.
[0033] Further preferably, when the current in the micro-area electrical treatment process is a pulse current, the temperature of the pulse recrystallization treatment is controlled to be (0.8Ts-200) to (0.8Ts-50)°C, and the time is 30 to 600s.
[0034] More preferably, the temperature of the electric pulse recrystallization treatment is 550-950° C., and the time is 30-300 s.
[0035] In the actual operation, the metal material that has been treated with gradient micro-area electrical control is placed in the processing equipment for electric pulse processing. Electric pulse processing refers to the process of providing electric pulse current to the electrified processing area of the sample from time to time during the processing.
[0036] In a preferred embodiment, the pulse power supply used in the electric pulse machining is a low-frequency high-peak-high-frequency low-peak dual-pulse power supply.
[0037] According to a preferred embodiment, the process of the electric pulse processing is as follows: a high-frequency low-peak pulse power supply is selected or a high-frequency low-peak pulse power supply is alternately switched with a low-frequency high-peak pulse power supply to perform a first electric pulse treatment on a layered gradient tissue material having an alternating distribution of "columnar crystal bands-equiaxed crystal bands". After the processing is completed, a low-frequency high-peak pulse power supply is adjusted to perform a second electric pulse treatment on the layered gradient tissue material having an alternating distribution of "columnar crystal bands-equiaxed crystal bands".
[0038] During the electric pulse processing of the present invention, a low-frequency high-peak-high-frequency low-peak dual pulse power supply is used. On the one hand, after the processing is completed, a low-frequency high-peak pulse power supply is used for electric pulse aging treatment to promote the precipitation of the second phase. On the other hand, during the processing, a high-frequency-low-frequency periodic switching can also be used, wherein a high-frequency low-peak pulse power supply is applied, and the effect of the pulse current on the material is mainly the electroplastic effect, which can effectively reduce the deformation resistance, and quickly refine the matrix grain size, eliminate the work hardening phenomenon, and thus improve the plastic toughness of the material. When a low-frequency high-peak pulse power supply is applied, the coupling effect of the Joule heating effect and the non-thermal effect of the pulse current is utilized to significantly promote the precipitation of the second phase, thereby improving the strength of the material.
[0039] Further preferred, the parameters of the low-frequency and high-peak pulse power supply used in the electric pulse processing are: output voltage: 6~12V; output current: 200~1000A; pulse frequency: 5000~20000Hz, and processing time: 0.01~300s; the parameters of the electric pulse using a high-frequency and low-peak dual pulse power supply are: output voltage: 6~12V; output current: 2000~5000A; pulse frequency: 20~2000Hz; processing time: 0.01~600s.
[0040] In a preferred solution, the electric pulse machining has a single-pass deformation of 5-30%, and a total deformation of >70%.
[0041] Further preferably, in the electric pulse machining, the deformation amount of a single pass is 5-15%, and the total deformation amount is greater than 90%.
[0042] The present invention utilizes electric pulse technology to eliminate in real time the phenomenon of significantly increased work hardening caused by dislocation entanglement and stacking during processing, thereby greatly reducing the deformation resistance of the material during the drawing process, improving the deformation capacity of the material, and facilitating subsequent large deformation processing and forming; at the same time, through the coupling effect of the Joule thermal effect and non-thermal effect of the electric pulse, the precipitation of second phase strengthening particles in the matrix is promoted, thereby improving the strength of the material and preparing a high-performance metal material.
[0043] Principles and advantages
[0044] High-energy electric pulse technology is a new process that can improve material organization and performance quickly and effectively in recent years. It uses the Joule heating effect and non-thermal effect of electric pulses to make metal materials undergo instantaneous high-energy non-equilibrium input, greatly promoting the movement of metal atoms and defects (vacancies, dislocations, grain boundaries, etc.). The current main work focuses on the following aspects:
[0045] 1) High-energy electric pulse treatment is applied to the liquid metal solidification process. When the metal material is in the solid-liquid two-phase region, high-energy electric pulse treatment can significantly increase the number of crystal nuclei, inhibit grain growth, obtain fine and uniform grains, and thus significantly improve the ingot structure.
[0046] 2) High-energy electric pulse treatment of solid metals. The microstructure and properties of the material can be regulated, including grain refinement, elimination of component segregation, and promotion of fine dispersion and precipitation of strengthening phases. In the metal processing process, by applying pulse current at both ends of the processed material, the deformation resistance of the material can be quickly and effectively reduced and the forming performance of the material can be improved.
[0047] Its working principle is to apply high-energy pulse current on both sides of the metal material, that is, the pulse power supply inputs the pulse current into the powered area of the metal material moving between the two electrodes through two electrodes, and the pulse current produces a coupling effect of Joule heating effect and non-thermal effect in the powered area of the metal material. The pulse current is used to significantly promote the atomic diffusion in the material and the strong interaction with defects (vacancies, dislocations, grain boundaries). On the one hand, it can improve the organizational structure of the material by quickly inducing recovery, recrystallization, phase change and other behaviors. On the other hand, it can improve the solidification organization of the metal material, refine the grains, improve the diffusion capacity of the elements, and promote the uniform distribution of the hard phase in the metal material; at the same time, by inputting the pulse current into the metal material between the two electrodes, the microstructure and performance of the material in the target area can be controlled.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] (1) Compared with the prior art, the present invention uses electric pulse directional solidification technology to prepare an ingot with a columnar crystal structure, replacing the equiaxed crystal structure in the material prepared by the traditional process. At the same time, directional solidification, electric pulse treatment, large deformation cold working, gradient micro-area electric treatment and electric pulse processing technology are organically combined. Directional solidification combined with electric pulse treatment is used to eliminate the component segregation phenomenon in single crystal or columnar crystal structure, and obtain a parallel columnar crystal structure with uniform composition; large deformation cold working is used to obtain high-density dislocation and other deformation structures, providing driving force for subsequent recrystallization, and combined with gradient micro-area electric treatment, the edge or core of the material is quickly recrystallized, the organizational morphology of specific areas is regulated, the matrix grain size is quickly refined, and the work hardening phenomenon is eliminated, which can greatly improve the plastic processing ability of the material and obtain a layered gradient structure with alternating distribution of "columnar crystals-equiaxed crystals"; then combined with electric pulse processing, high-density dislocations and fine dispersed second phase particles are introduced at the same time to achieve dynamic balance control of "dislocation multiplication-dislocation annihilation-second phase precipitation", which effectively solves the limitations of metal materials subject to specific performance requirements (such as hard outside and tough inside, strong and tough alternation) and size requirements, and obtains high-performance metal materials.
[0050] (2) Compared with the existing metal material preparation process, the present invention provides a layered gradient structure of "columnar crystal-equiaxed crystal" alternating distribution to replace the traditional columnar crystal or equiaxed crystal, which can achieve the simultaneous improvement of material strength and plastic toughness; in the traditional processing process, due to the increase in deformation resistance, the deformation amount of each pass gradually decreases, and many processing passes are required. After processing, a large number of dislocations and fiber structures are generated, and a long-term aging process is required. However, the present invention organically combines electric pulses with processing technology, and adopts a periodic control method to replace the multiple deformation + heat treatment processes faced in the existing "processing-annealing-processing-aging", which significantly reduces the deformation resistance, texture strengthening, dislocation entanglement and other phenomena, greatly improves the deformation amount of the alloy, reduces the processing steps, and obtains high-strength and high-toughness metal materials, solving the problems of long and complicated existing process flow, high energy consumption, and high cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It is a process flow chart of the present invention.
[0052] Figure 2 This is the microstructure diagram of Example 1, in which the white area is equiaxed crystals, and the dark area is columnar crystals. It can be seen that equiaxed crystals and columnar crystals are distributed alternately. DETAILED DESCRIPTION
[0053] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and equipment involved in this article can be purchased from the market or prepared by known methods.
[0054] Example 1
[0055] A metal sheet, strip layer gradient structure control process and application, the process flow is as follows Figure 1 As shown, the following steps are included:
[0056] This embodiment is based on Cu-Ni-Sn copper alloy.
[0057] (1) Electric pulse directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. The crucible is induction heated by an electromagnetic coil, and the heating temperature is controlled at 1300°C. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for stirring at a stirring speed of 500r / min. Then lower the temperature to 1180°C for insulation. After 5 minutes of insulation, turn on the pulse power supply, and set the pulse frequency to 800Hz and the current density to 6.0A / cm through the central controller. 3 After 5 minutes of processing time, the pulse power supply was turned off. Then, the molten metal was pulled out from the center hole of the gallium-indium cooling crystallizer at 16°C by a mechanical arm linkage traction rod at a speed of 1 mm / s to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0058] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0059] (3) Gradient micro-area control: The cold-rolled billet is divided into alternating columnar crystal regions and equiaxed crystal regions along the length direction, and the equiaxed crystal regions are subjected to micro-area electrical processing, wherein the width ratio of the columnar crystal region to the equiaxed crystal region is 1:1.5. The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe, and the probe uses a circular contactor with a contact area of 0.5 mm2 A low-frequency, high-peak pulse power supply is selected, with an equivalent voltage of 6V and a current of 600A. The temperature of the electric pulse recrystallization treatment is 780°C, the time is 60s, and the treatment is continued at intervals of 2mm until the entire equiaxed crystal area is processed.
[0060] (4) Electric pulse rolling: The plate with the layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on the rolling mill for electric pulse rolling, and the electric pulse aging is completed during the rolling process. During rolling, first select the high-frequency low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; output current to: 200A; pulse frequency to 10000Hz, and processing time to 120s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, select the low-frequency high-peak gear pulse power supply, set the output voltage to: 8V; output current to: 2000A; pulse frequency to 200Hz; processing time to 60s.
[0061] The performance indicators of the alloy plate and strip in this implementation case are:
[0062] Tensile strength: 1820MPa
[0063] Elongation at break: 15.6%
[0064] Electrical conductivity: 17.1% IACS
[0065] Embodiment 2:
[0066] A metal sheet, strip layer gradient structure control process and application, the process flow is as follows Figure 1 As shown, the following steps are included:
[0067] This embodiment takes titanium alloy as the object.
[0068] (1) Electric pulse directional solidification: Prepare titanium particles, aluminum particles and vanadium blocks with a purity of 99.99% or more according to the mass ratio of Ti:Al:V=90:6:4, and put V, Ti, and Al into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. The crucible is induction heated by an electromagnetic coil, and the heating temperature is controlled at 1380°C. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for mechanical stirring at a stirring speed of 500r / min. Then reduce the temperature to 1100°C for insulation. After 5 minutes of insulation, turn on the pulse power supply, and set the pulse frequency to 1000Hz and the current density to 4.0A / cm through the central controller. 3After 5 minutes of processing time, the pulse power supply was turned off. Then, the molten metal was pulled out from the center hole of the gallium-indium cooling crystallizer at 16°C by a mechanical arm linkage traction rod at a speed of 1 mm / s to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0069] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0070] (3) Gradient micro-area control: The cold-rolled billet is divided into alternating columnar crystal regions and equiaxed crystal regions along the length direction, and the equiaxed crystal regions are subjected to micro-area electrical processing, wherein the width ratio of the columnar crystal region to the equiaxed crystal region is 1:2. The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe, and the probe uses a circular contactor with a contact area of 0.5 mm 2 , select low-frequency high-peak pulse power supply, equivalent voltage of 6V, current of 800A, temperature of electric pulse recrystallization treatment of 780℃, time of 60s. Continue the treatment at intervals of 2mm until the entire equiaxed crystal area is processed.
[0071] (4) Electric pulse rolling: The plate with the layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on the rolling mill for electric pulse rolling, and the electric pulse aging is completed during the rolling process. During rolling, first select the high-frequency low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; output current to: 250A; pulse frequency to 15000Hz, and processing time to 90s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, select the low-frequency high-peak gear pulse power supply, set the output voltage to: 8V; output current to: 2000A; pulse frequency to 200Hz; processing time to 60s.
[0072] The performance indicators of the alloy plate and strip in this implementation case are:
[0073] Tensile strength: 1440MPa
[0074] Elongation at break: 18.8%
[0075] Embodiment 3:
[0076] A metal sheet, strip layer gradient structure control process and application, the process flow is as follows Figure 1 As shown, the following steps are included:
[0077] This embodiment is based on Cu-Be copper alloy.
[0078] (1) Electric pulse directional solidification: Prepare pure beryllium and electrolytic copper with a purity of 99.99% or more according to the mass ratio of Be:Cu=2.5:97.5, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. The crucible is induction heated by an electromagnetic coil, and the heating temperature is controlled at 1300℃. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for mechanical stirring at a stirring speed of 500r / min. Then lower the temperature to 1180℃ for insulation. After 5 minutes of insulation, turn on the pulse power supply, and set the pulse frequency to 1000Hz and the current density to 6.0A / cm through the central controller. 3 After 5 minutes of processing time, the pulse power supply was turned off. Then, the molten metal was pulled out from the center hole of the gallium-indium cooling crystallizer at 16°C by a mechanical arm linkage traction rod at a speed of 1 mm / s to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0079] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0080] (3) Gradient micro-area control: The cold-rolled billet is divided into alternating columnar crystal regions and equiaxed crystal regions along the length direction, and the equiaxed crystal regions are subjected to micro-area electrical processing, wherein the width ratio of the columnar crystal region to the equiaxed crystal region is 1:2. The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe, and the probe uses a circular contactor with a contact area of 0.5 mm 2 , select low-frequency high-peak pulse power supply, equivalent voltage of 6V, current of 800A, temperature of electric pulse recrystallization treatment of 880℃, time of 60s. Continue the treatment at intervals of 2mm until the entire equiaxed crystal area is processed.
[0081] (4) Electric pulse rolling: The plate with the layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on the rolling mill for electric pulse rolling, and the electric pulse aging is completed during the rolling process. During rolling, first select the high-frequency low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; output current to: 200A; pulse frequency to 10000Hz, and processing time to 120s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, select the low-frequency high-peak gear pulse power supply, set the output voltage to: 8V; output current to: 2500A; pulse frequency to 400Hz; processing time to 60s.
[0082] The performance indicators of the alloy plate and strip in this implementation case are:
[0083] Tensile strength: 1320MPa
[0084] Elongation at break: 15.6%
[0085] Electrical conductivity: 27.1% IACS
[0086] Example 4
[0087] This comparative example takes Cu-Ni-Sn copper alloy as the object and adopts traditional directional solidification instead of electric pulse directional solidification.
[0088] (1) Directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. The crucible is induction heated by an electromagnetic coil, and the heating temperature is controlled at 1300℃. After the metal block in the crucible is melted into a metal melt, the electromagnetic stirrer is turned on for mechanical stirring at a stirring speed of 500r / min. Then the temperature is lowered to 1180℃ for insulation. After insulation for 5 minutes, the metal melt is pulled out from the central hole of the gallium-indium cooling crystallizer at 16℃ by a mechanical arm linkage traction rod at a speed of 1mm / s to form a 60×20mm alloy ingot with "parallel" slender columnar crystals.
[0089] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0090] (3) Gradient micro-area control: The cold-rolled billet is divided into alternating columnar crystal regions and equiaxed crystal regions along the length direction, and the equiaxed crystal regions are subjected to micro-area electrical processing, wherein the width ratio of the columnar crystal region to the equiaxed crystal region is 1:2. The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe, and the probe uses a circular contactor with a contact area of 0.5 mm 2 A low-frequency, high-peak pulse power supply is selected, with an equivalent voltage of 6V and a current of 600A. The temperature of the electric pulse recrystallization treatment is 780°C, the time is 60s, and the treatment is continued at intervals of 2mm until the entire equiaxed crystal area is processed.
[0091] (4) Electric pulse rolling: The plate with the layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on the rolling mill for electric pulse rolling, and the electric pulse aging is completed during the rolling process. During rolling, first select the high-frequency low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; output current to: 200A; pulse frequency to 10000Hz, and processing time to 120s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, select the low-frequency high-peak gear pulse power supply, set the output voltage to: 8V; output current to: 2000A; pulse frequency to 200Hz; processing time to 60s.
[0092] The performance indicators of the alloy plate and strip in this implementation case are:
[0093] Tensile strength: 1670MPa
[0094] Elongation at break: 12.6%
[0095] Electrical conductivity: 13.2% IACS
[0096] Comparative Example 1:
[0097] This comparative example takes Cu-Ni-Sn copper alloy as the object and adopts traditional solid solution treatment to replace the gradient micro-area control treatment process.
[0098] (1) Electric pulse directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. Turn on the water cooler, set the crystallizer circulating water flow rate to 1000L / h, and induction heat the crucible through the electromagnetic coil. The heating temperature is controlled at 1300℃. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for mechanical stirring at a stirring speed of 500r / min. Then reduce the temperature to 1180℃ for insulation. After 5 minutes of insulation, turn on the pulse power supply, set the pulse frequency to 800Hz and the current density to 6.0A / cm through the central controller. 3 After 5 minutes of processing time, the pulse power supply was turned off. Then, the molten metal was pulled out from the center hole of the gallium-indium cooling crystallizer at 16°C by a mechanical arm linkage traction rod at a speed of 1 mm / s to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0099] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0100] (3) Solution treatment: Place the plates and strips after large deformation cold rolling into a box-type resistance furnace for solution treatment at a holding temperature of 780°C for 4 hours.
[0101] (4) Electric pulse rolling: The plate with the layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on the rolling mill for electric pulse rolling, and the electric pulse aging is completed during the rolling process. During rolling, first select the high-frequency low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; output current to: 200A; pulse frequency to 10000Hz, and processing time to 120s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, select the low-frequency high-peak gear pulse power supply, set the output voltage to: 8V; output current to: 2000A; pulse frequency to 200Hz; processing time to 60s.
[0102] The performance indicators of the alloy plate and strip in this implementation case are:
[0103] Tensile strength: 1410MPa
[0104] Elongation at break: 6.6%
[0105] Electrical conductivity: 8.8% IACS
[0106] Comparative Example 2:
[0107] This comparative example uses Cu-Ni-Sn copper alloy as the object, and adopts traditional cold rolling + aging treatment instead of electric pulse rolling treatment process.
[0108] (1) Electric pulse directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. Turn on the water cooler, set the crystallizer circulating water flow rate to 1000L / h, and induction heat the crucible through the electromagnetic coil. The heating temperature is controlled at 1300℃. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for mechanical stirring at a stirring speed of 500r / min. Then reduce the temperature to 1180℃ for insulation. After 5 minutes of insulation, turn on the pulse power supply, set the pulse frequency to 800Hz and the current density to 6.0A / cm3 through the central controller, and turn off the pulse power supply after the processing time is 5 minutes. Subsequently, the molten metal was pulled out from the center hole of the 16°C gallium-indium cooling crystallizer at a speed of 1 mm / s using a robotic arm-linked traction rod to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0109] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0110] (3) Gradient micro-area control: The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe. The probe uses a circular contactor with a contact area of 0.5 mm 2 , select low-frequency high-peak pulse power supply, equivalent voltage of 6V, current of 600A, temperature of electric pulse recrystallization treatment of 780℃, time of 60s. Continue the treatment at intervals of 2mm, and complete it after 30 treatments in sequence.
[0111] (4) Cold rolling: The plate with a layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on a six-roll rolling mill for cold rolling. The total deformation is 90%, the single-pass deformation is 10%, and the plate thickness reaches 0.2 mm after multiple rolling.
[0112] (5) Traditional aging treatment: The cold-rolled plates and strips are placed in a box-type resistance furnace for aging and insulation treatment at a temperature of 400°C for 2 hours.
[0113] The performance indicators of the alloy plate and strip in this implementation case are:
[0114] Tensile strength: 1420MPa
[0115] Elongation at break: 13.6%
[0116] Electrical conductivity: 13.1% IACS
[0117] Comparative Example 3:
[0118] This comparative example takes Cu-Ni-Sn copper alloy as the object, and adopts traditional cold rolling + electric pulse aging treatment to replace the electric pulse rolling treatment process.
[0119] This embodiment is based on Cu-Ni-Sn copper alloy.
[0120] (1) Electric pulse directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. Turn on the water cooler, set the crystallizer circulating water flow rate to 1000L / h, and induction heat the crucible through the electromagnetic coil. The heating temperature is controlled at 1300℃. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for mechanical stirring at a stirring speed of 500r / min. Then reduce the temperature to 1180℃ for insulation. After 5 minutes of insulation, turn on the pulse power supply, set the pulse frequency to 800Hz and the current density to 6.0A / cm3 through the central controller, and turn off the pulse power supply after the processing time is 5 minutes. Subsequently, the molten metal was pulled out from the center hole of the 16°C gallium-indium cooling crystallizer at a speed of 1 mm / s using a robotic arm-linked traction rod to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0121] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0122] (3) Gradient micro-area control: The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe. The probe uses a circular contactor with a contact area of 0.5 mm 2 , select low-frequency high-peak pulse power supply, equivalent voltage of 6V, current of 600A, temperature of electric pulse recrystallization treatment of 780℃, time of 60s. Continue the treatment at intervals of 2mm, and complete it after 30 treatments in sequence.
[0123] (4) Cold rolling: The plate with a layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation is placed on a six-roll rolling mill for cold rolling. The total deformation is 90%, the single-pass deformation is 10%, and the plate thickness reaches 0.2 mm after multiple rolling.
[0124] (5) Electric pulse aging treatment: The cold-rolled plates and strips are placed in an electric pulse heat treatment furnace for electric pulse aging. A low-frequency, high-peak pulse power supply is selected, and the output voltage is set to 8V; the output current is 2000A; the pulse frequency is 200Hz; and the treatment time is 60s.
[0125] The performance indicators of the alloy plate and strip in this implementation case are:
[0126] Tensile strength: 1560MPa
[0127] Elongation at break: 15.6%
[0128] Electrical conductivity: 14.6% IACS
[0129] Comparative Example 4:
[0130] This comparative example uses a Cu-Ni-Sn copper alloy as the object, and only uses a high-frequency power supply for processing during the electric pulse rolling process.
[0131] This embodiment is based on Cu-Ni-Sn copper alloy.
[0132] (1) Electric pulse directional solidification: Prepare electrolytic copper sheets, nickel sheets and tin blocks with a purity of 99.99% or more according to the mass ratio of Ni: Sn: Cu = 15: 8: 77, and put Ni, Cu, and Sn into the electric pulse directional solidification crucible in order from high to low according to the melting point, and then put 20g of sodium carbonate with a particle size of 5 mesh to cover the metal surface. The crucible is induction heated by an electromagnetic coil, and the heating temperature is controlled at 1300°C. After the metal block in the crucible is melted into a metal melt, turn on the electromagnetic stirrer for stirring at a stirring speed of 500r / min. Then lower the temperature to 1180°C for insulation. After 5 minutes of insulation, turn on the pulse power supply, and set the pulse frequency to 800Hz and the current density to 6.0A / cm through the central controller. 3 After 5 minutes of processing time, the pulse power supply was turned off. Then, the molten metal was pulled out from the center hole of the gallium-indium cooling crystallizer at 16°C by a mechanical arm linkage traction rod at a speed of 1 mm / s to form a 60×20 mm alloy ingot with "parallel" slender columnar crystals.
[0133] (2) Large deformation cold rolling: The ingot is subjected to large deformation cold rolling along the temperature gradient direction. The deformation of a single pass is 20%, the total deformation is 90%, and the thickness of the slab reaches 2 mm after multiple rolling.
[0134] (3) Gradient micro-area control: The cold-rolled billet is divided into alternating columnar crystal regions and equiaxed crystal regions along the length direction, and the equiaxed crystal regions are subjected to micro-area electrical processing, wherein the width ratio of the columnar crystal region to the equiaxed crystal region is 1:1.5. The cold-rolled alloy sheet is subjected to micro-area electrical processing using an oxygen-free copper electronic probe, and the probe uses a circular contactor with a contact area of 0.5 mm 2 A low-frequency, high-peak pulse power supply is selected, with an equivalent voltage of 6V and a current of 600A. The temperature of the electric pulse recrystallization treatment is 780°C, the time is 60s, and the treatment is continued at intervals of 2mm until the entire equiaxed crystal area is processed.
[0135] (4) Electric pulse rolling: Place the plate with a layered gradient structure of "columnar crystal-equiaxed crystal-columnar crystal-equiaxed crystal" after gradient micro-area regulation on the rolling mill for electric pulse rolling, and complete electric pulse aging during the rolling process. During rolling, first select the high-frequency and low-peak gear in the dual-frequency pulse power supply, set the output voltage to: 8V; the output current to: 200A; the pulse frequency to 10000Hz, and the processing time to 120s; after setting the parameters, turn on the rolling mill, set the single-pass deformation to 10%, the total deformation to 90%, and roll it into a strip with a thickness of 0.2mm. After rolling is completed, continue to select the high and low peak gear pulse power supply, set the output voltage to: 8V; the output current to: 200A; the pulse frequency to 10000Hz; the processing time is 60s. The performance indicators of the alloy plate and strip in this implementation case: tensile strength: 984MPa
[0136] Elongation at break: 16.8%
[0137] Electrical conductivity: 8.4% IACS.
Claims
1. A method for preparing a metal material having a layered gradient structure, characterized in that: Metal raw materials are selected according to the composition of the metal material, the metal raw materials are smelted to obtain a metal melt, the metal melt is directionally solidified to obtain an ingot with a columnar crystal structure, the ingot is cold-processed, the cold-processed part is subjected to micro-area electrical treatment to obtain a layered gradient structure material with alternating distribution of "columnar crystal bands-equiaxed crystal bands", and finally the layered gradient structure material is subjected to electrical pulse processing to obtain a metal material with a layered gradient structure.
2. The method for preparing a metal material having a layered gradient structure according to claim 1, characterized in that: Metal raw materials are placed into a crucible in descending order according to their melting points, a covering agent is placed on the surface of the crucible, and smelting is performed to obtain a metal melt, wherein the covering agent is selected from one of sodium carbonate, borax, sodium fluoride, cryolite, and graphite powder.
3. The method for preparing a metal material with a layered gradient structure according to claim 1 or 2, characterized in that: The smelting process is to first melt the metal raw material at 700-2000°C to obtain a melt, mechanically stir the melt, then cool it to 650-1550°C, keep it warm for 5-10 minutes, and then apply an electric pulse to obtain a metal melt; The rotation speed of the mechanical stirring is 0.1-1000 r / min. The frequency of the electric pulse is 200~3500Hz, and the current density is 0.1~50A / cm 3 .
4. The method for preparing a metal material with a layered gradient structure according to claim 1 or 2, characterized in that: The directional solidification process is: using an axial speed of 1 to 100 mm / min to make the metal melt pass through a cooling crystallizer in sequence, wherein the cooling medium used in the cooling crystallizer is selected from one of water, 16° C. gallium-indium coolant, and liquid nitrogen alcohol circulating coolant. The columnar crystal structure is selected from one of parallel type, figure eight type and vertical type.
5. The method for preparing a metal material with a layered gradient structure according to claim 1 or 2, characterized in that: During the cold working, the working direction is controlled to be the direction of the temperature gradient; During the cold working, the deformation per pass is 5% to 30%, and the total deformation is 50 to 95%; The cold working is selected from one of cold rolling, cold drawing, cold forging, cold rotary forging, cold radial forging, cold extrusion and cold heading.
6. The method for preparing a metal material with a layered gradient structure according to claim 1, characterized in that: The cold-worked billet is divided into an alternating columnar crystal region and an equiaxed crystal region along the length direction or the width direction, and the equiaxed crystal region is subjected to micro-area electrical treatment, wherein the micro-area electrical treatment parameters are: voltage of 0.01 to 30 V, and current of 0.01 to 10000 A; The width ratio of the columnar crystal region to the equiaxed crystal region is 1:1-2.
7. The method for preparing a metal material with a layered gradient structure according to claim 1 or 6, characterized in that: The current form in the micro-area electrical treatment process is any one of pulse current, constant current, alternating current and direct current.
8. The method for preparing a metal material with a layered gradient structure according to claim 1 or 6, characterized in that: The micro-area electrical treatment process applies an electric current to the cold-worked blank through a movable electronic probe, places the movable electronic probe in the equiaxed crystal area of the cold-worked blank, applies a current once within the area of the electronic probe, and then moves the electronic probe in parallel to apply a current to the next area of the electronic probe. After one equiaxed crystal area is treated, the electronic probe is moved to the next untreated equiaxed crystal area and the above process is repeated; any one current application time is 0.01 to 20 minutes; The shape of the electronic probe is any one of a rectangular, circular, elliptical, and linear shape; the shape of the electronic probe is any one of a rectangular, circular, elliptical, and linear shape; The area of the electronic probe is 0.01 to 10 mm 2 .
9. The method for preparing a metal material with a layered gradient structure according to claim 1, characterized in that: The pulse power supply used in the electric pulse machining is a low-frequency high-peak-high-frequency low-peak double pulse power supply. The process of the electric pulse processing is: selecting a high-frequency low-peak pulse power supply or alternately switching between a high-frequency low-peak pulse power supply and a low-frequency high-peak pulse power supply to perform a first electric pulse processing on a layered gradient tissue material with an alternating distribution of "columnar crystal bands-equiaxed crystal bands", and after the processing is completed, adjusting to a low-frequency high-peak pulse power supply to perform a second electric pulse processing on the layered gradient tissue material with an alternating distribution of "columnar crystal bands-equiaxed crystal bands"; The parameters of the low-frequency high-peak pulse power supply used in the electric pulse processing are: output voltage: 6~12V; output current: 200~1000A; pulse frequency: 5000~20000Hz, and processing time: 0.01~300s; the parameters of the electric pulse using a high-frequency low-peak double pulse power supply are: output voltage: 6~12V; output current: 2000~5000A; pulse frequency: 20~2000Hz; processing time: 0.01~600s.
10. The method for preparing a metal material with a layered gradient structure according to claim 1 or 9, characterized in that: The electric pulse machining has a single-pass deformation of 5-30% and a total deformation of more than 70%.
Citation Information
Patent Citations
Hard alloy surface treatment method and application
CN110343993A
A method for preparing a high-strength, high-toughness, conductive copper alloy strip
CN111424224B
Preparation method of composite copper-based metal strip
CN117358754A